From new order to regional autonomy: shifting dynamics of "illegal" logging in Kalimantan, Indonesia - Casson, A.; Obidzinski, K. (2002)
In recent years there has been a tendency to view the seemingly irremediable spread of "illegal" logging in Indonesia in isolation, or as a result of disassociated and premediated criminal acts. This paper proposes a different view of the problem by discussing the changing dynamics of the "illegal" logging sector in the two districts of Berau, East Kalimantan and Kotawaringin Timur, Central Kalimantan. It suggests that illegal logging is not a simple case of criminality, but a complex economic and political system involving multiple stakeholders. Furthermore, "illegal" logging is not a stationary condition that can be effectively dealt with through coersive or repressive measures alone. Rather, it should be viewed as a dynamic and changing system deeply engrained in the realities of rural life in Indonesia. Regional autonomy has also created a supportive environment for the "illegal" logging trade and allowed it to gain resilience.